Digital Marketing Untuk Tingkatkan Visibilitas Layanan Sosial Bagi Pekerja Sosial Masyarakat Desa Kota Batu - Syamsul Bakhri; Aswar Hanif; Yayan Hendrian; Markus Lilik Martanto (Jurnal Abdimas Perbanas, 2023)
The importance of digital marketing training for village community social workers in Batu City to increase the visibility of the social services they offer. In an increasingly advanced digital era, social workers must utilize digital technology to promote the social services they provide so that they can be more easily accessed by the public. Digital marketing training can help village community social workers in Batu City to expand their reach of social services and increase support from the community. This community service activity explains several digital marketing strategies that can be used by social workers such as websites, social media, email newsletters, and Google My Business. In addition, this training also provides tips on how to choose the right digital marketing platform to promote social services. Digital marketing training is very important for village community social workers in Batu City to increase the visibility of the social services they offer and gain support from the community. By leveraging digital technology, social workers can more effectively promote social services and achieve better results in providing support to rural communities in Batu City.